Identidade do lugar na percepção socioambiental dos moradores em assentamentos rurais de Mato Grosso - Lessa, Dayse de Jesus (2017)
The current research aims to know the identity of the place through the socioenvironmental perception of the producers, applied to the territorial management of natural resources and productive activities in the Fazenda Esperança and Padre Jozimo settlements both located in Rondonópolis, Mato Grosso. The investigation is characterized as of the human geography with the application of the perception study to evaluate the degree of satisfaction with the place of the rural settlers. The conceptual basis is based mainly on the concept of place and territory. The application of the concept of territory in the present time is well differentiated, because not only have their contexts changed, just as science itself has sought other paradigms and methods and, consequently, new challenges. The idea of place is presented as a phenomenon concerning the dynamics of geographical space and the dimensions of identities and affectivities that are not always considered in geographic studies. From this perspective, through semi-structured interviews with thirty residents of the Fazenda Esperança and Padre Jozimo Settlements, it was verified that 90% of the residents are satisfied with the place. Regarding Identity and Meaning of Place, 58% responded that nature means everything and 42% responded that it means a means of survival. Concerning Problems and Desires, it was observed that 50% of the problems reported by the interviewees refers to the lack of government support that encourages productive work, as well as basic attention to essential services such as health and education. Thus, based on numbers, we realize that settlement is the livelihood, labor, and survival for these families. The property or lot received in the settlement is also a place of great satisfaction for the residents of both settlements, being in the same proportion of affection as the house. Settlement is another place scale which for the residents had diverse meanings for interviewees of both settlements. The data analyzed in the two settlements point to the satisfaction and belonging of the residents with the place, in almost all aspects, except in aspects of infrastructure, health services and production, that is, external demands their wills and decisions. This information is important for the municipal and state public policies aimed at the settlements and municipalities involved in the research. In sum, there are strong topfilic feelings and belonging of the settlers with the various scales of place analyzed, indicating a high degree of satisfaction and identity of place.